Determinants of household debt in Malaysia from the year 2010 to 2017 / Zahariah Mohd Zain, Nurul Ainun Ahmad Atory and Sarah Amirah - Mohd Zain, Zahariah; Ahmad Atory, Nurul Ainun; Hanafi, Sarah Amirah (Universiti Teknologi MARA Cawangan Selangor, 2019)
Household debt has become an issue in the Malaysian economy as it affects the country socially and economically.This study aims to examine the determinants of household debt from the year 2010 until 2017. This study employs the Ordinary Least Square (OLS) method and the macroeconomic variables used in this study are Gross Domestic Product (GDP), base lending rate, unemployment and housing price as independent variables. The results indicate that the trend of household debt in Malaysia has shown a continuous rise from the year 2010 to 2017. GDP, base lending rate and housing price indicate a positive relationship towards household debt while unemployment shows a negative relationship to household debt in Malaysia. All explanatory variables have shown a significant relationship except for GDP. Housing price has been found to be the most significant factor and positively related to household debt. The findings indicate that the higher the price of houses, the higher the household debt will be.